Pendahuluan Menggagas Prototipe Mushaf Al-qur’an Standar Indonesia Riwayat Qalun Menurut Tharîq al-syâthibiyyah - Hadi, Sofyan (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2021)
This research was written with the aim of presenting a manuscript of the Al-Qur'an which is easily accessible to the Muslim community in Indonesia in studying and practicing reading the Qur'an from the history of Qalun through the initial step in the form of "Prototype of Indonesian Standard Al-Qur'an Manuscripts. The History of Qalun according to Tharîq al. -Syâtibiyyah ”.In this study, the findings of differences in the reading of the history of Hafsh and the history of Qalun according to tharîq al-Syâthibiyyah are presented, both in terms of general principles (ushyliyyah) and certain readings in certain verses and letters (farsy al-hurûf). In the ushûliyyah rule, the difference is in the mim jama 'rule, ha` kinâyah, idghâm saghîr, mad munfashil, two hamzah in one word, two hamzah in two words, ya` idhâfah, ya` zâidah, and the word التَّوْرٰىةَ. As for the difference in farsy al-hurûf there are certain words in certain verses, such as the word; ملك, يخدعون, يكذبون.Furthermore, the findings related to the punctuation marks (dhabth) applied to the Indonesian Standard Al-Qur`an Manuscripts of the history of Hafsh and several Al-Quran manuscripts of the history of Qalun circulating in the Islamic world today, including the Mushaf al-Jamâhîriyyah History of Qalun from Libya. Madinah al-Munawwarah, Jordan, Tunisia and Egypt. In general, the use of punctuation marks (dhabth) in these manuscripts follows the dhabth ulama of the masyâriqah or maghâribah school with reference books including: al-Thirâz 'alâ Dhabth al-Kharrâz by al-Tanasi, Dalîl al-Hairân' ala al-Kharraz by al-Maraghini, Al-Muhkam by al-Dani.The most interesting thing in this dissertation is the finding that the punctuation marks (dhabth) in the Indonesian Standard Al-Qur'an Manuscripts which are adapted to the qiraat narrations of Hafsh can be applied to qiraat narrations of Qalun by means of; (1) Keep using the punctuation mark (dhabth) which has been standardized in the Indonesian Standard Al-Qur'an Mushaf which is still relevant to be applied to qiraat narrations of Qalun; (2) Modifying its use in qiraat narrations of Qalun; (3) Creating a new punctuation mark (dhabth) that does not exist in the Indonesian Standard Al-Qur'an Mushaf.This research is in line with the Indonesian Standard Al-Qur'an Mushaf in several ways, namely related to rasm, count of verses and punctuation marks (dhabth) and in line with the Mushaf Application of al-Taysîr bi al-Qirâ`at al-'Asyr from Hazim's Qalun history. al-Barduni in terms of the face of the recitation of Qalun shillah mim jama 'ma'a al-qashr on the other hand, the findings of this study are different from the existing Indonesian Standard Mushaf (MSI) because MSI is in accordance with Hafsh's history reading, whereas in this dissertation it produces MSI according to the reading of Qalun's history. The difference with the Manuscripts of the application of al-Taysîr bi al-Qirâ`at al-'Asyr by Hazim al-Barduni and several manuscripts of Qalun history from abroad that exist in the world today is that the use of rhymes, verse counts, and punctuation in findings This dissertation is adapted to what MSI already exists.This research is a qualitative research through library research with a comparative study approach. The primary source of this research is the Standard Indonesian Al-Qur'an Manuscripts and several Al-Qur'an Manuscripts from Qalun from several countries, Hirz al-Amâniy Wa Wajh al-Tahâniy fî al-Qirâ`ât al-Sab 'by al-Qasim. bin Fiyrruh Bin Khalaf Bin Ahmad al-Syathibiy al-Ra'ainiy al-Andalusiy (d. 590 H), and Al-Mukhtashar al-Jâmi 'li Ushûl Riwâyât Qâlûn' an Nâfi 'by Abd al-Halim Muhammad Al-Hadi Qabah.